Vitamin A toxicity and hypercalcaemia in chronic renal failure. Issue 6281 (20th June 1981) - Farrington, K; Miller, P; Varghese, Z; Baillod, R A; Moorhead, J F
Abstract : Serum vitamin A concentrations were measured in 38 patients undergoing haemodialysis, 24 of whom were taking multivitamin preparations containing vitamin A. Vitamin A concentrations were significantly higher in patients undergoing haemodialysis than in 28 normal controls (p less than 0.001). Patients taking vitamin A supplements had significantly higher vitamin A concentrations than those not taking them (p less than 0.05), and hypercalcaemic patients had higher concentrations than normocalcaemic patients (p less than 0.005). Withdrawal of vitamin A supplements in seven patients caused significant falls in serum vitamin A concentrations and plasma calcium concentrations (p less than 0.01 at two and three months in both cases) and in plasma alkaline phosphatase concentrations (p less than 0.01 at two months). Vitamin A toxicity can contribute to hypercalcaemia in patients undergoing haemodialysis, probably by an osteolytic effect. Multivitamin preparations containing vitamin A should therefore be prescribed with caution in these patients.